1999
DOI: 10.1073/pnas.96.10.5412
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of a multifunctional protein: Phosphoglucose isomerase/autocrine motility factor/neuroleukin

Abstract: Phosphoglucose isomerase (PGI) plays a central role in both the glycolysis and the gluconeogenesis pathways. We present here the complete crystal structure of PGI from Bacillus stearothermophilus at 2.3-Å resolution. We show that PGI has cell-motility-stimulating activity on mouse colon cancer cells similar to that of endogenous autocrine motility factor (AMF). PGI can also enhance neurite outgrowth on neuronal progenitor cells similar to that observed for neuroleukin. The results confirm that PGI is neuroleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 60 publications
5
88
1
3
Order By: Relevance
“…For instance, hexokinase, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and enolase have been implicated to play a role in transcriptional regulation (Niederacher and Entian, 1991;Herrero et al, 1995;Feo et al, 2000;Rodriguez et al, 2001;Zheng et al, 2003). Hexokinase and GAPDH may regulate apoptosis (Ishitani and Chuang, 1996;Shashidharan et al, 1999;Tajima et al, 1999;Dastoor and Dreyer, 2001;Gottlob et al, 2001;Pastorino et al, 2002;Rathmell et al, 2003;Majewski et al, 2004), and glucose-6-phosphate isomerase can affect cell motility (Liotta et al, 1986;Nabi et al, 1990;Watanabe et al, 1996;Niinaka et al, 1998;Sun et al, 1999). Furthermore, although glycolysis is the classical metabolic pathway that generates pyruvate, other metabolic reactions such as conversion of xylulose-5-phosphate to glyceraldehyde-3-phosphate through the pentose phosphate pathway by transketolase also produce the metabolic intermediate that channel to the second phase of the glycolytic pathway ( Figure 1, dashed arrows), yielding pyruvate and ATP.…”
Section: The Glycolytic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, hexokinase, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and enolase have been implicated to play a role in transcriptional regulation (Niederacher and Entian, 1991;Herrero et al, 1995;Feo et al, 2000;Rodriguez et al, 2001;Zheng et al, 2003). Hexokinase and GAPDH may regulate apoptosis (Ishitani and Chuang, 1996;Shashidharan et al, 1999;Tajima et al, 1999;Dastoor and Dreyer, 2001;Gottlob et al, 2001;Pastorino et al, 2002;Rathmell et al, 2003;Majewski et al, 2004), and glucose-6-phosphate isomerase can affect cell motility (Liotta et al, 1986;Nabi et al, 1990;Watanabe et al, 1996;Niinaka et al, 1998;Sun et al, 1999). Furthermore, although glycolysis is the classical metabolic pathway that generates pyruvate, other metabolic reactions such as conversion of xylulose-5-phosphate to glyceraldehyde-3-phosphate through the pentose phosphate pathway by transketolase also produce the metabolic intermediate that channel to the second phase of the glycolytic pathway ( Figure 1, dashed arrows), yielding pyruvate and ATP.…”
Section: The Glycolytic Pathwaymentioning
confidence: 99%
“…Interestingly, recent studies have revealed that GPI can also function as an autocrine motility factor (AMF), which is secreted from the tumor cells to promote cell motility and proliferation (Niinaka et al, 1998;Sun et al, 1999). Autocrine motility factor and its receptor AMFR (gp78) were originally identified in melanoma and oncogenetransfected metastatic NIH3T3 cells, and the AMF/ AMFR interaction seems to stimulate tumor cell migration in vitro and enhance metastasis and angiogenesis in vivo (Liotta et al, 1986;Nabi et al, 1990;Watanabe et al, 1996;Funasaka et al, 2001Funasaka et al, , 2002.…”
Section: Glucose-6-phosphate Isomerasementioning
confidence: 99%
“…About 120 mg of GPI protein with 99% of purity were obtained from 1 liter of cell culture. In gel filtration chromatography, the MW of GPI protein was estimated to be 130 kDa (Figure 3), which suggested that GPI protein was present as homodimers in the solution as previously described (Sun et al, 1999).…”
Section: R Esultsmentioning
confidence: 97%
“…The recombinant GPI protein appears to have the intact conformation of the natural counterpart based on some physical characeristics. First, the recombinant GPI protein was purified as dimers as previously reported (Sun et al, 1999). NusA-GPI protein was purified as tetramers, but since NusA protein itself was produced as dimers, NusA-GPI protein was also presumed to reflect the intact stoichiometry of GPI protein.…”
Section: Discussionmentioning
confidence: 99%
“…Il sera nécessaire pour cela d'obtenir un Cependant, le cas de la LEI s'inscrit dans un cadre beaucoup plus large qui reste à explorer. Ce changement de fonction par modification conformationnelle n'est pas rare dans le monde des protéines et, dans plusieurs travaux récents, on commence à analyser les bases structurales de cette pluripotentialité [40]. La famille des serpines est particulièrement concernée puisque la modification conformationnelle fait partie intégrante du fonctionnement de ces inhibiteurs de protéases.…”
Section: Conclusion Perspectivesunclassified